Kontektualisasi Nilai-Nilai Sila Pertama Pancasila dalam Al-Qur’an dan Problematika Implementasi - Hendro Juwono; Fawait Syaiful Rahman (MOMENTUM : Jurnal Sosial dan Keagamaan, 2021)
Abstract In addition to the moral decline, the sense of nationalism as a citizen also experienced the same thing. Attitudes and actions that do not reflect good citizens of the State often characterize the State of Indonesia. One example is the act of discrimination from the majority group to the minority group. Indonesia was built by diversity, not individuals. Through a joint consensus by the nation's founding fathers, not the common people. All forms of discrimination are not allowed either according to Islamic law or the rules that apply in a country. In Indonesia, the rules regarding freedom to embrace religion and belief are regulated in Law no. 39 of 1999 concerning Human Rights. The method used is a qualitative method with a literature approach, and the analysis uses descriptive. The results of the analysis show that Pancasila values ​​are the essence of the feeling of the condition of the Indonesian nation. The value of the first precepts of Pancasila is in synergy with the moral message behind the text of the verse and the substance of the teachings of Islam itself. The value of the first precepts of Pancasila becomes the foundation for the following precepts. Everything is in synergy with each other and there is no contradiction. In the context of internalizing the values ​​of Pancasila, there are at least three implementation problems. The first is the problem of implementing basic values, the second is the value of the instrument, and the third is the practical value.